2019
DOI: 10.1002/jnr.24426
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding of presbycusis

Abstract: The pathophysiology of age‐related hearing loss (ARHL), or presbycusis, involves a complex interplay between environmental and genetic factors. The fundamental biomolecular mechanisms of ARHL have been well described, including the roles of membrane transport, reactive oxygen species, cochlear synaptopathy, vascular insults, hormones, and microRNA, to name a few. The genetic basis underlying these mechanisms remains under‐investigated and poorly understood. The emergence of genome‐wide association studies has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 123 publications
(161 reference statements)
0
22
0
Order By: Relevance
“…Cochlear ion channels play a critical role in maintaining normal hearing. They are crucial for supporting hair cell development, maintaining the endocochlear potential (EP) and synaptic transmission (Tawfik et al, 2019;Fuchs, 1996). Many studies have identified plenty of mutations in membrane transport proteins which result in progressive hearing loss with age (Tawfik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear ion channels play a critical role in maintaining normal hearing. They are crucial for supporting hair cell development, maintaining the endocochlear potential (EP) and synaptic transmission (Tawfik et al, 2019;Fuchs, 1996). Many studies have identified plenty of mutations in membrane transport proteins which result in progressive hearing loss with age (Tawfik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Presbycusis arises in the inner ear (Keithley, 2019;Tawfik et al, 2019;Fischer et al, 2020), where sound is transduced, by inner hair cells (IHCs), into electrical signals carried by auditory nerve fibers (ANFs) to the brain (Fig. 1A,C).…”
Section: Introductionmentioning
confidence: 99%
“…Age-related hearing loss involves numerous risk factors ranging from genetics to lifestyle, with the underlying mechanisms remaining largely unknown. However, damage to the auditory receptors in the cochlea, namely the inner and outer hair cells (IHCs and OHCs) and their innervation, is likely to play a key role (Johnsson, 1974;Schuknecht & Gacek, 1993;Sergeyenko et al 2013;Tawfik et al 2019;Wu et al 2019;Jimenez et al 2020). Although we now have a better understanding of age-related changes in OHCs (Jeng et al 2020a) and IHC ribbon synapses (Jeng et al 2020b), very little is known about how the biophysical properties of IHCs and their efferent innervation are affected by cochlear ageing, which limits our understanding of how IHC function contributes to the progression of ARHL.…”
Section: Introductionmentioning
confidence: 99%